2017
DOI: 10.1021/acs.jpcc.7b00130
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Nanoreactors of Au@Fe3O4 Yolk–Shell Nanostructures with Various Au Sizes for Efficient Nitroarene Reduction

Abstract: Au@Fe3O4 yolk–shell nanocatalysts based on the thermal decomposition of iron pentacarbonyl in the presence of 2.5–10-nm Au core nanoparticles were successfully fabricated for the catalytic reduction of nitroarenes. The particle sizes of the Au@Fe3O4 nanostructures were in the range 8–15 nm, with Fe3O4 shell layer thicknesses of 2.0–2.4 nm. The Fe3O4 layer not only can form a magnetic shell for recovery but also enables the protection of the catalytic activity of the Au core nanoparticles toward the reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…Moreover, Av-AuNPs acted as a redox catalyst in the degradation/reduction of organic pollutants and dyes by electron relay effect between donor and acceptor molecules. Various reports 23,39,[41][42][43][44][45][46][47][48] are available on catalytic activity of gold nanoparticles for the reduction of major organic pollutant 4-NP and degradation of organic dyes MB, MO and DB24. From the reports (Table 2), it is clear that as the size of the gold nanoparticle decreases the required time span for the reduction or degradation of organic pollutant or dyes also decreases with increasing catalytic efficiency.…”
Section: Degradation Of Rhodamine 6g (Rh6g)mentioning
confidence: 99%
“…Moreover, Av-AuNPs acted as a redox catalyst in the degradation/reduction of organic pollutants and dyes by electron relay effect between donor and acceptor molecules. Various reports 23,39,[41][42][43][44][45][46][47][48] are available on catalytic activity of gold nanoparticles for the reduction of major organic pollutant 4-NP and degradation of organic dyes MB, MO and DB24. From the reports (Table 2), it is clear that as the size of the gold nanoparticle decreases the required time span for the reduction or degradation of organic pollutant or dyes also decreases with increasing catalytic efficiency.…”
Section: Degradation Of Rhodamine 6g (Rh6g)mentioning
confidence: 99%
“…94 In another report, AgNPs induced inflammatory response in neuronal cells. 9 It was reported that AgNPs entered the nuclei of mouse neuronal cells and induced progression of neurodegenerative disorder. 9 It was reported that silver nitrate treatment increased cellular superoxide dismutase activity and decreased mitochondrial membrane potential, leading to neuronal death.…”
Section: Inhibitory Effect Of Nanoparticles On Neuronal Cellsmentioning
confidence: 99%
“…[1][2][3] Nanoparticles can be synthesized in different sizes (1.0-500 nM) and shapes (cones, cubes, rods, tubes, and shells). [4][5][6] There are various applications of nanoparticles in biotechnology, biosensing, catalysis, magnetic fluids, separation techniques, energy storage, and environmental modification [7][8][9][10][11][12] and also in biomedical field, especially in diagnostics, and drug or gene delivery. [13][14][15][16][17][18][19] Interestingly, nanoparticles have been extensively used as drug carrier systems for therapeutic molecules with the primary aim to improve the therapeutic effect and decrease their side effects and drug/gene delivery.…”
Section: Introduction Of Nanoparticlesmentioning
confidence: 99%
“…The conversion of 4‐NP (4‐nitrophenol, substrate A) through absorption spectroscopy for different nanocomposites has been reported as model catalytic reaction as the absorbance change of this reagent is simplistic to monitor . Similar to these studies, repetitive reduction cycles of 4‐NP and more than 90% conversation for each reaction cycle up to 8 cycles (Figure S15) in presence of catalyst 5Fe suggest the stability and reusability of 5Fe in the reaction condition.…”
Section: Resultsmentioning
confidence: 66%